A autonomia universitária após trinta anos da Constituição Federal de 1988 = The university autonomy after thirty years of the 1988 Federal Constitution - Cavalieri, Davi Valdetaro Gomes (2020)
Submitted by rafaelrn@stj.jus.br (rafaelrn@stj.jus.br) on 2020-06-08T22:22:05Z No. of bitstreams: 2 autonomia_universitaria_trinta_cavalieri.pdf: 524006 bytes, checksum: 718f20683a9a89de99c780da10dc6e83 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)